(3GdOQI GdjJjeI aj GdejbGJs - (3YHO Gddg Hf CMeO GdefGhj GdTGaYj,J (B1060 (3g` s
(3ChdgG (B:s
(3jbhd YHO Gddg fLd CMeOG Hf GdefGhi GdTGaYi ai GdGHJOG s
(3BNQgG (B:s
(3CHjGJgG ai GdYO NGJe aG hYO HGdVHW dgPG GdCdaG s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B21s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B972 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs